Visceral Fat Affects Heart Rate Recovery but Not the Heart Rate Response Post-Single Bout of Vigorous Exercise: A Cross-Sectional Study in Non-Obese and Healthy Participants - Alessandra Amato; Luca Petrigna; Martina Sortino; Giuseppe Musumeci (Sports)
Body composition could influence exercise physiology. However, no one has ever studied the effect of visceral fat (VF) on heart rate (HR) trends during and after exercise by using bioimpedance analysis (BIA). This study aims to investigate BIA variables as predictors of HR trends during vigorous exercise. Ninety-six participants (age 22.5 ± 4.8 years) were included in the data analysis. After performing BIA, the HR was recorded at three time points: baseline HR (BHR), peak HR (PHR) at the end of vigorous exercise, and resting HR (RHR) 1 min after the end of the exercise. After BHR, a 30 s squat jump test was performed. Linear regression analysis showed the body fat percentage and VF as a predictor of HR recovery post-exercise (p < 0.01). However, body weight has no association with HR recovery (p > 0.05). On the other hand, BIA variables were not associated with the variation of HR from the baseline to the end of the exercise. The results show that higher VF is associated with a slower HR recovery. To schedule a training program, it would be safer to monitor visceral fat before prescribing recovery time.